Mental health protecting recreational physical education model for 40-50-plus year-olds - Makhmutova, R.K.; Prichinin, A.E.; Baranov, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze benefits of a new mental health protecting recreational physical education model for the 40-50-plus year-olds. Methods and structure of the study. We sampled for study the 43-52 year-olds (n=87) and split them up into Experimental Group (20 men and 24 women) reporting habitual (at least three times a week) fitness trainings; plus non-sporting Reference Group of 22 men and 21 women. We used the following tests: Mini-Mult Psychological Test adapted by F.B. Berezin and M.P. Miroshnikov; Physical Activity Rating Test; and the L.I. Wasserman Anxiety Test; plus a standard statistical data processing toolkit. Results and conclusion. The new mental health protecting recreational physical education model for the 40-50-plus year-olds analyzed gives a special priority to the socializing factors among the mental health protection tools – to complement the predominant studies of the age group’s physical health and mental health risk factors. The recreational mental-health-improvement model for adults was found beneficial. We would recommend the study data and analyses being taken into account by the studies geared to motivate different age groups, including the mature and older ones, for physical development and sporting lifestyles in the social contexts that encourage every individual physical education and sports agenda.